2012
DOI: 10.1177/0748730412442830
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Modulates Enamel Development

Abstract: Fully mature enamel is about 98% mineral by weight. While mineral crystals appear very early during its formative phase, the newly secreted enamel is a soft gel-like matrix containing several enamel matrix proteins of which the most abundant is amelogenin (Amelx). Histological analysis of mineralized dental enamel reveals markings called cross-striations associated with daily increments of enamel formation, as evidenced by injections of labeling dyes at known time intervals. The daily incremental growth of ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 50 publications
(70 reference statements)
4
71
0
3
Order By: Relevance
“…Investigators studying the circadian rhythm of transcript abundance in mouse molars determined that NBCe1 transcript abundance is nearly doubled during dark periods compared with light periods (537). The authors suggest that this observation correlates with periods of enhanced enamel deposition by ameloblasts (537).…”
Section: B) Increased Transcript Abundance During Dark Periodsmentioning
confidence: 99%
“…Investigators studying the circadian rhythm of transcript abundance in mouse molars determined that NBCe1 transcript abundance is nearly doubled during dark periods compared with light periods (537). The authors suggest that this observation correlates with periods of enhanced enamel deposition by ameloblasts (537).…”
Section: B) Increased Transcript Abundance During Dark Periodsmentioning
confidence: 99%
“…The observed circadian regulation of adult hippocampal neurogenesis (Bouchard-Cannon et al, 2013) could complement circadian regulation of dendritic spine formation and stabilization (Liston et al, 2013), allowing for more efficient reintegration of new neurons into the adult brain. A circadian clock is also present in tooth ameloblasts, where it controls antiphase rhythms of enamel matrix endocytosis and secretion, as well as ameloblast maturation (Lacruz et al, 2012;Zheng et al, 2013). Circadian oscillations in the release of hematopoietic stem cells (HSCs), coupled with antiphase circadian expression of the chemokine Cxcl12 and coordinated with GSK3β-dependent changes in HSC migratory properties (Lapid et al, 2013), could result in the coordinated release of HSCs and repopulation of the bone marrow stem cell niche (Méndez-Ferrer et al, 2009.…”
Section: From Cell Cycle To Tissues: Circadian Control Of Tissue Homementioning
confidence: 99%
“…Of significance, amelogenin expression still oscillates under DD conditions, however in less extend and with a slight shift in peak times [31]. In vitro studies have also confirmed that amelogenin expression is modulated by clock genes [31, 34, 35] (Fig. 2).…”
Section: Expression and Potential Roles Of The Circadian Clock In Minmentioning
confidence: 95%